Analysis and evaluation of shape memory alloy wires behaviour in weft-knitted fabrics - Medeiros, J. I. (2013)
It is widely acknowledged within the textile engineering community that Shape Memory Alloys (SMA), exhibit great potential for several applications. This paper presents the research undertaken at the University of Minho aiming to study the behaviour of weft-knitted fabrics produced with SMA nitinol® wires. SMA nitinol® wires of type B (which shows shape memory effect at body temperature) of 50, 127 and 210 μm diameters have been used to produce weftknitted fabrics with different loop types, e.g. stitch, tuck and miss. The influence of the loop type on the performance of the weft-knitted fabric, in terms of energy absorption, has been analyzed. Tensile tests were carried out according to ISO1462 standard, using a H100KS Hounsfield universal testing instrument. The results aim to help future applications of SMA in the development of new textile materials.